Measurements of Liquid AISI 304L Steel Density and Surface Tension, and Influence of Surface‐Active Elements at High Temperatures. Issue 6 (17th January 2022) - Delacroix, Jules; Piluso, Pascal; Chikhi, Nourdine; Asserin, Olivier; Borel, Damien; Brosse, Alexandre; Cadiou, Stephen
Abstract : Within the framework of the welding of steel components in pressurized water reactors, the optimization of the weld pool penetration is a major issue. The thermal‐hydraulics of the molten steel pool can be driven by Marangoni flows at the free surface. To compute these flows, liquid steel's thermophysical properties such as density ρ and surface tension σ are required. Such properties for austenitic vessel steel AISI 304L at liquid state are scarce, and even not available above 1800 °C, due to technological issues. The viscometer temperature installation (VITI) is designed to implement sessile droplet (SD) and maximum bubble pressure (MBP) techniques. These techniques allow to determine original ρ and σ data for two grades of AISI 304L steel, namely 304LP1 and 304LP4—low and high sulfur content, at various temperatures. In particular, thanks to the innovative design of MBP configuration, original surface tension data are obtained from the melting point up to 2100 °C. For the first time, experimental evidence of the Sahoo et al.'s (1988) model at high temperature is provided, emphasizing the decisive role played by surface‐active elements such as sulfur and oxygen on surface tension, whose content evolution is assessed by dedicated chemical analyses. Abstract : The measurements performed on two high‐temperature apparatuses provide new insights into the density and surface tension of liquid steels, leading to original correlations, and highlighting the decisive role of surface‐active elements such as sulfur and oxygen on surface tension.